Arthrodesis of a Distal Interphalangeal Joint in a wild African Buffalo (Syncerus caffer) - Shakespeare, Anthony Scott (Journal of Buffalo Science, 2015)
Intensification of wild ruminants has resulted in more lameness cases that are presented for medical and surgical intervention. Claw problems in these wild and often dangerous animals, although similar to those seen in domestic bovines often require quick decisions and speedy adaptations of generally accepted treatment and procedure protocols. The arthrodesis of the pedal joint in a buffalo cow is one such example.